2018
DOI: 10.17338/trainology.7.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-day reliability of a Wattbike cycle ergometer sprint protocol in male rugby players

Abstract: Objective: The purpose of this study was to establish the inter-day reliability of several performance variables measured during a 2 × 6 s sprint on a Wattbike cycle ergometer in male rugby players. Reliablilty was assessed against an 'analytical goal' of detecting meaningful changes that might be expected with fatigue in rugby. Design & Methods:Sixteen male rugby players performed three trials of the protocol on different days seperated by a mimimum of 48 h. The protocol comprised 2 × 6 s 'all out' cycle spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In addition, a reliability study on the Wattbike 6 s cycle sprint found that “total work”, in Cals, was the most reliable measure. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a reliability study on the Wattbike 6 s cycle sprint found that “total work”, in Cals, was the most reliable measure. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The measurement of “total work” is calculated from the distance per revolution multiplied by the force with the result record in calories (Cals). 19 The number of repetitions where PPO stayed above 95% (PPO95+) were recorded. Performance decrement (%Dec) in performance was calculated after the completion of each of the three trials using the following formula as outlined by previously 10 : %Dec = 1 − (sum of sprints 1 to 10/best sprint × 10) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…The 6sCS test consisted of 2 x 6 s sprints with 90 s recovery on a calibrated cycle ergometer (WattBike Pro, Nottingham, UK) using a protocol previously shown to be reliable with a Coefficient of Variation (CV) of 4.2% for peak power (Cushman et al, 2018). A five-minute warmup was completed before the test; whereby players pedaled at a self-selected light (RPE of 3) resistance at a cadence of 80 rev•min -1 , with a mandated 2-s maximal acceleration at the 3-, 4-and 5-minute mark.…”
Section: Six-second Cycle Testmentioning
confidence: 99%
“…Individual effort duration in Rugby Union is typically less than 4 s at all intensities (Lacome et al, 2013). An alternative assessment, the six-second peak power test on a cycle ergometer (6sCS) has increased in popularity as a testing and training tool (Cushman et al, 2018;Jones et al, 2019;Wehbe et al, 2015). The shorter duration of the 6sCS may be a more practical and relevant test than the WAnT as it has a lower technical requirement with a duration similar to typical maximal and ballistic strength tests.…”
Section: Introductionmentioning
confidence: 99%